PENGARUH LITERASI DIGITAL DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA USAHA UMKM: (Studi pada UMKM SEKTOR Food and Beverage di Jakarta Selatan) - Muhamad Tsani Farhan; Henry Eryanto; Ari Saptono (Transpublika Publisher, 2022)
The purpose of this study was to determine the effect of digital literacy and entrepreneurial orientation on the business performance of MSMEs in the food and beverage sector in South Jakarta. The variables used in this study are digital literacy as an independent variable, entrepreneurial orientation as a mediating variable (intervening), and MSME business performance as the dependent variable. The sample used in this study amounted to 114 SMEs in the food and beverage sector. The sampling method used is the proportional random sampling method, with the path analysis method. The results of this study indicate that digital literacy and entrepreneurial orientation have a positive and significant impact on MSME business performance, as well as digital literacy mediated by entrepreneurial orientation on MSME business performance in the food and beverage sector in South Jakarta. In line with the results of this study, it is recommended that MSME business actors in the food and beverage sector in South Jakarta should further increase their insight into digital technology literacy because there are still quite a number of related MSMEs that have not mastered digital technology massively. Furhermore, it is also necessary to have an entrepreneurial orientation such as the ability to innovate, risk taking, and be aggressive in good competition in order to achieve healthy and competitive business performance.